Making Global Value Chains Work for Development - Taglioni, Daria; Winkler, Deborah (World Bank, Washington, DC, 2014)
Global value chains (GVCs) are playing an increasingly important role in business strategies, which has profoundly changed international trade and development paradigms. GVCs now represent a new path for development by helping developing countries accelerate industrialization and the servicification of the economy. From a firm perspective, production in the context of GVCs highlights the importance of being able to seamlessly connect factories across borders, as well as protect assets such as intellectual property. From the policy maker perspective, the focus is on shifting and improving access to resources while also advancing development goals, and also on the question of whether entry into GVCs delivers labor-market-enhancing outcomes for workers at home, as well as social upgrading. GVCs can lead to development, but, at the country level, constraints such as the supply of various types of labor and skills and inadequate absorptive capacity remain. GVCs can create new opportunities on the labor demand side, but supply and demand cannot meet if the supply is missing. This potential gap illustrates the importance of embedding national GVC policies into a broader portfolio of policies aimed at upgrading skills, physical and regulatory infrastructure, and enhancing social cohesion.